Association between Virulence Factors and Extended Spectrum Beta-Lactamase Producing Klebsiella pneumoniae Compared to Nonproducing Isolates - Mustafa Muhammad Gharrah; Areej Mostafa El-Mahdy; Rasha Fathy Barwa (Interdisciplinary Perspectives on Infectious Diseases)
Klebsiella pneumoniae is considered an important opportunistic multidrug-resistant pathogen. Extended spectrum β-lactamases (ESBLs) and expression of a multitude of virulence factors may work in a harmony resulting in treatment failure. This study was undertaken to compare the virulence characteristics and genetic relatedness between ESBL and non-ESBL producing K. pneumoniae. Methods. Antibiotic sensitivity test of all isolates was determined by disc diffusion assay. Phenotypic and genotypic detection of ESBL were done. Various virulence factors and some virulence factor-associated genes were screened. Random amplified polymorphic DNA (RAPD) was employed to investigate the genetic fingerprints of ESBL from non-ESBL producing K. pneumoniae. Results. 50% of isolates were ESBL producers. A significant association was observed between ESBL production and biofilm (strong and moderate), serum resistance, and iss gene. Moreover, significant association between non-ESBL producers and hypermucoviscosity was identified. Dendogram analysis of RAPD profile classified K. pneumoniae isolates into four clusters (a, b, c, and d). Seventy-six percent of ESBL producers belonged to cluster a. In conclusion, this study suggests a correlation between ESBL production and some virulence factors. Therefore, success of treatment depends mainly on increased clinicians awareness and enhanced testing by laboratories to reduce the spread of these isolates.